Hubungan antara Kepuasan Sekolah dan Subjective Well-Being Siswa SMP di Kota Bandung pasca COVID-19 - Anggresya Syifa Novatiana; Ihsana Sabriani Borualogo (Bandung Conference Series: Psychology Science, 2023)
Abstract. School satisfaction contributes to adolescent life satisfaction, especially given the importance of the school environment and the amount of time students spend at school. To measure adolescents' school satisfaction and life satisfaction, the most important thing is what happens during their daily life at school. The purpose of this study was to find out how satisfaction with school and SWB of junior high school students in Bandung City was post-COVID-19 and wanted to find out what was the relationship between school satisfaction and SWB in junior high school students in Bandung City after COVID-19. This research uses quantitative research methods. The sampling technique used is cluster random sampling. This study used measurement tools from Children's World, namely School Satisfaction, CW-SWBS5 and OLS. This study involved 965 students with a percentage of students namely 57.1% female students and 42.9% male students. The results show that male students (M = 82.7%) are more satisfied with their school than female students (M = 77.7%). Junior high school students in Bandung City overall had slightly above average satisfaction with school (M = 79.86), and their SWB was slightly above average (M = 75.16). Satisfaction as a school student is the factor that contributes most to students' overall life satisfaction, and satisfaction with what is learned at school is the factor that contributes most to their SWB. Abstrak. Kepuasan sekolah berkontribusi terhadap kepuasan hidup remaja, terutama mengingat pentingnya lingkungan sekolah dan jumlah waktu yang dihabiskan siswa di sekolah. Untuk mengukur kepuasan sekolah dan kepuasan hidup remaja, hal yang paling penting adalah apa yang terjadi selama kehidupan sehari-hari mereka di sekolah. Tujuan dari penelitian ini ingin mengetahui bagaimana kepuasan terhadap sekolah dan SWB siswa SMP di Kota Bandung pasca COVID-19 serta ingin mengetahui bagaimana hubungan antara kepuasan sekolah dengan SWB pada siswa SMP di Kota Bandung pasca COVID-19. Penelitian ini menggunakan metode penelitian kuantitatif. Teknik sampling yang digunakan yaitu cluster random sampling. Penelitian ini menggunakan alat ukur dari Children’s World yaitu School Satisfaction, CW-SWBS5 dan OLS. Penelitian ini melibatkan 965 siswa dengan persentase siswa yaitu 57.1% siswa perempuan dan 42.9% siswa laki-laki. Hasil menunjukkan bahwa siswa laki-laki (M = 82.7%) lebih puas dengan sekolah mereka daripada siswa perempuan (M= 77.7%). Siswa SMP di Kota Bandung secara keseluruhan memiliki kepuasan terhadap sekolah yang sedikit di atas rata-rata (M = 79.86), dan SWB mereka sedikit di atas rata-rata (M = 75.16). Kepuasan sebagai murid sekolah adalah faktor yang paling berkontribusi terhadap kepuasan kehidupan siswa secara keseluruhan, dan kepuasan dengan apa yang dipelajari di sekolah adalah faktor yang paling berkontribusi terhadap SWB mereka.